CBDC web Binus university as an educational media to promote environmental ethics awareness - Fios, Frederikus; Gea, Antonius Atosokhi; Ruman, Yustinus Suhardi; Maku, Hendrikus (Edelweiss Applied Science and Technology, 2025)
The issue of our environment is never finished being discussed. The environment needs to be discussed because it is related to the future fate of humankind and other species of living things. For us humans, global environmental pollution threatens human health and demands education about ethical attitudes to preserve the natural environment. Ethical education, especially in the current digital era, is very important to support sustainable development in the future. The purpose of this study is to determine the possibility of environmental ethics in the writing of articles on the CBDC Binus University website. This research uses philosophical methods, especially a critical hermeneutic approach to analyze articles on the Character-Building Development Center (CBDC) website of Bina Nusantara University, Indonesia. The finding is that this website precipitates meaningful epistemological knowledge relevant to environmental ethics. The Binus CBDC website promotes environmental ethics, as evidenced by the existence of more than 100 articles written by lecturers and students, which discuss philosophical, religious, legal, and socio-cultural perspectives in preserving the environment. This research provides new insights into efforts to save the environment in the context of higher education and society in the digital era, especially for young people studying at universities to be aware of and carry out environmental love movements that have a real impact on the environment and humans.